(untitled) (Singaporean Journal of Business Economics and Management, 2015)
This study aims to predict the audience’s perception of cultural television channel was cultural capital. All students of the humanities research community to the number of 6428 people formed the University of Isfahan. Of these 362 patients was calculated by the Cochran formula were selected through stratified random sampling method. Data collection tools to measure cultural capital of a questionnaire of 28 questions in three dimensions Objectified, Embodied, and institutional and questionnaire 9 questions the perception of quality. The validity of the questionnaire structure and reliability verified through Cronbach’s alpha coefficient scale cultural capital (0.86) and to the perception of quality (0.78) were estimated. Regression results show that the best predictor of an institution in the first step and the second step in addition to the following institutional Objectified cultural capital dimension. The findings also showed no significant difference in demographic variables between these variables was found with Perception and cultural capital.